Seasonal variation in milk yield, fat and SNF content of Murrah crossbred buffalo in mid-western Terai region of Nepal - Bhattarai, N. (Journal of Agriculture and Forestry University, 2020)
A research was done during July 2016 to June 2017 for a period of one year at Baijanath Rural Municipality, Banke district of mid-western terai region of Nepal to analyze the seasonal variation in average daily milk yield (DMY), standard 305 days milk yield (SMY), fat percent and solid-not-fat (SNF) percent in the milk of crossbred Murrah buffaloes. A total of 1086 milk sample was purposively collected from 235 lactating crossbred Murrah buffaloes of early (first and second) parity and were analyzed for major quality traits of milk covering four seasons- spring (February to April), summer (May to July), autumn (August to October), and winter (November to January). Results revealed that season had significant influence on DMY (p<0.05), SMY (p<0.01), fat (p<0.01) and SNF (p<0.01) content of crossbred Murrah buffaloes. Accordingly, highest DMY and SMY was recorded for the buffaloes calved in spring season with highest fat and SNF content during summer and spring season, respectively. Thus, results of this study reflected a scientific fact about wider variation in milk yield, fat and SNF contents in Murrah buffaloes with the significant effect of season. This information could be useful in recognizing the importance of synchronizing calving dates during spring season for higher production and productivity in order to maintain the quality aspects of milk, such as fat and SNF content. Further investigation is, however, required regarding genetic parameters determination of these traits covering wider population in the region.